2011
DOI: 10.1007/s10554-010-9766-1
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of coronary artery hyperemic blood flow based on arterial lumen volume using angiographic images

Abstract: The purpose of this study is to develop a method to estimate the hyperemic blood flow in a coronary artery using the sum of the distal lumen volumes in a swine animal model. The limitations of visually assessing coronary artery disease are well known. These limitations are particularly important in intermediate coronary lesions where it is difficult to determine whether a particular lesion is the cause of ischemia. Therefore, a functional measure of stenosis severity is needed using angiographic image data. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
(82 reference statements)
1
14
0
Order By: Relevance
“…In contrast, the exponent ␤ in our study decreased from 0.79 to 0.55 for truncation radii ranging from 50 to 1,000 m. A value of 3/4 (0.75) for the exponent was previously suggested based on the measured relationship between flow and segment length and the derived relationship between segment length and cumulative arterial volume (31). This value was validated by angiographic imaging at the limited resolution of 500 m (7,15,30). Using theoretical derivation based on rules for branching at bifurcations, a value of 7/9 (0.78) has been suggested (4), which agrees well with ␤ ϭ 0.79 found at our smallest truncation radius (50 m).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In contrast, the exponent ␤ in our study decreased from 0.79 to 0.55 for truncation radii ranging from 50 to 1,000 m. A value of 3/4 (0.75) for the exponent was previously suggested based on the measured relationship between flow and segment length and the derived relationship between segment length and cumulative arterial volume (31). This value was validated by angiographic imaging at the limited resolution of 500 m (7,15,30). Using theoretical derivation based on rules for branching at bifurcations, a value of 7/9 (0.78) has been suggested (4), which agrees well with ␤ ϭ 0.79 found at our smallest truncation radius (50 m).…”
Section: Discussionsupporting
confidence: 67%
“…These relationships are expressed in terms of allometric scaling laws relating, among others, coronary flow to myocardial mass (1), cumulative arterial branch length, stem diameter, or the total crown volume, as summarized elsewhere (4). Using this last method, FFR prediction is based on the hypothetical flow in the absence of the stenosis, as estimated from the luminal volume of the arterial tree distal to the stenosis (7). The rationale of this approach is that larger vascular trees perfuse larger myocardial volumes and therefore transport more flow.…”
mentioning
confidence: 99%
“…Several noninvasive modalities have been developed for assessing CFR and FFR such as PET, MRI, CT, transthoracic Doppler echocardiography, and synchrotron radiation (SR) imaging. 19 In the case of flow measurement using PET, the measured flow is normalized by the myocardial mass (ml/min/100 g of tissue). Although PET offers unique clinical insight, such as the assessment of myocardial viability and perfusion, it is a complex and expensive technology and remains primarily an investigative tool.…”
Section: Estimation Of CC Using Angiographic Imagesmentioning
confidence: 99%
“…However, volumetric coronary blood flow and the calculated resistance are dependent on the arterial perfusion bed size. Previous reports (21,25) have shown that the arterial lumen volume is related to the myocardial mass and can be used to account for the dependent arterial bed size. Therefore, the normalized MR (NMR) (43) can be calculated as:…”
Section: Methodsmentioning
confidence: 99%